Medical education during the coronavirus disease pandemic and students’ mental health: A one-year follow-up - Bolatov, Aidos K.; Seisembekov, Telman Z.; Dauyenov, Ernur; Zhorokpayeva, Meiramgul D.; Smailova, Dariga S.; Pavalkis, Dainius (Frontiers in Education, 2022)
Background The coronavirus disease (COVID-19) pandemic has affected medical education and psychosomatic health of medical students. In this follow-up study, conducted 1 year after the transition to online learning (OL), we aimed to investigate changes in student mental health and identify factors associated with academic burnout and changes in medical education caused by the pandemic. Materials and methods This study compares the burnout rate and psychosomatic status (depression, anxiety, somatic symptoms) of medical students at Astana Medical University using an online questionnaire-based repeated cross-section design of the pre-pandemic period (September–November 2019), the initial period of the pandemic (April 2020), and the current study (March 9–30, 2021). In the pre-pandemic period, students studied only in a face-to-face format. Moreover, the current study (March, 2021) analyzed factors associated with academic burnout and changes in medical education caused by the pandemic. Statistical methods included mean comparison, frequency, and regression analysis. Results Data from a representative sample of undergraduate students were analyzed (n = 975, 58% of them participated in the previous study). The burnout rate was found to be lower compared with the period of traditional education (pre-COVID-19) and did not significantly differ from the initial period of the introduction of online learning (the initial period of the COVID-19 pandemic). The levels and prevalence of depression and anxiety also showed similar patterns. The prevalence of somatic symptoms has increased compared to the initial period of the pandemic, although it has not reached the level obtained in the pre-COVID-19 period. The negative changes caused by OL in medical education and learning effectiveness have been associated with burnout. Factors associated with burnout, learning effectiveness, dissatisfaction with the quality of OL organization, and deterioration of medical education have been identified. Conclusion The medical education and mental health of medical students has undoubtedly undergone changes in the transition to OL due to the COVID-19 pandemic. Factors such as changing the content of education, the organization of the educational process and support from the school, the nature of student-teacher, student-school and student-student relationships, the possibility of mastering various skills and financial problems caused by the pandemic, played a significant role in the academic life of students. The results obtained have potential applications in organizing and improving the quality of continuing medical education in an era of global healthcare crises such as the COVID-19 pandemic.